Global Jihad and the Tactic of Terror Abduction : a comprehensive review of Islamic terrorist organizations - Shay, Shaul (Brighton : Sussex Academic Press, 2015)
"In recent decades, the taking of hostages has proven to be a particularly effective tactic for Islamic terrorist organizations worldwide, including al Qaeda. The global jihad movement regards citizens of foreign (mainly Western) countries as prime targets for abduction, although in fact local residents have constituted the majority of kidnapping victims. This book analyzes Islamic terror abductions over the last 30 years in the Middle East (Lebanon, Syria, Iraq, Iran, Yemen, and Saudi Arabia), Asia (Afghanistan, Pakistan, India, and the Philippines), Africa (the Maghreb, the Sahel regions, and Somalia), and in Russia as a part of the Russian-Chechen conflict. Discussion also focuses on the abduction by Hizballah of Israeli soldiers, the "Second Lebanon War" of 2006, the Mumbai terror attack, the Chechen hostage crises in Moscow and Beslan, and the kidnapping of employees of the Algerian In Amenas gas facility by "al Qaeda of the Maghreb." The discussion focuses on the challenges faced by countries whose citizens have been abducted by Islamic terror organizations and their reactions to these challenges, providing theoretical classifications of the phenomenon of terrorism in general and terror abduction in particular"--
Includes bibliographical references and index.
Keywords: Qaida (Organization); Political kidnapping; Islamic fundamentalism; Jihad; Political science -- Political freedom & security; Political science -- Political freedom & security -- Terrorism